Compared to What? Menstruation, Pregnancy, and the Complexities of Comparison - Waldman, Emily Gold (Columbia Journal of Gender and Law, 2021)
This piece explores the complexities of the comparative model as applied to sex discrimination claims that are connected to female biology. On the one hand, comparisons can be a useful and precise way to pinpoint discrimination. The notion that bandages and adult diapers are tax-exempt, while tampons and pads are not, brings the unfairness of the tampon tax into sharp relief: Why are those products for absorbing bodily fluids tax-free, when menstrual products are not? The same is true for a pregnant employee who can show that her request for a light-duty accommodation was denied while the identical light-duty request by another similarly-situated, non-pregnant employee was granted. But the model also contains two traps. First, almost no comparison is perfect. There is often some potential for distinguishing and line-drawing, some way to argue that the comparison does not fully hold up. Second, the comparative model is itself inherently limiting. The biological processes of menstruation and pregnancy (along with menopause and breastfeeding, which this piece does not address) are closely intertwined with female sex and have no obvious analogues. Indeed, these processes impose specific challenges and needs that are not borne equally across the sexes. Yet the comparative model reductively suggests that if no products receive tax-exempt status, or if no employees receive accommodations for their inability to work, there is no sex discrimination issue at all. Although advocates cannot escape the current comparative framework within which they must work—and indeed should use it to their advantage when possible—we should all remain mindful of the framework’s ultimate limitations. The piece begins by analyzing Young v. United Parcel Service, Inc., the 2015 Supreme Court case that grappled with how to apply the PDA’s comparison-based standard. I discuss how Young illustrates the complexities of comparison and unpack the compromise approach that emerged. I then consider the potential usefulness of the Young approach to the tampon tax cases, while acknowledging that they arise under the Equal Protection Clause rather than Title VII. I conclude with some broader reflections.